Dyslipidemia, statins and prostate cancer. Issue 7 (July 2012) - Rice, Kevin R; Koch, Michael O; Cheng, Liang; Masterson, Timothy A
Dyslipidemia and prostate cancer are two of the most common medical conditions affecting adult males in the USA. In recent years, a large volume of research has focused on investigating the relationship between these two disease processes as well as the effect of the cholesterol-lowering medications, such as 3-hydroxyl-3-methylglutaryl-coenzyme A reductase inhibitors (better known as 'statins'), on the development and progression of prostate cancer. While there is a paucity of prospective research, encouraging results have been reported in several retrospective clinical studies. Additionally, basic science research has identified interactions between lipids and prostate cancer cells in several key areas. This article will discuss recent clinical and basic science research examining the relationship between dyslipidemia, statins and prostate cancer.